Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1046/j.1365-2583.1999.810097.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequence variation among populations and host races of Lambdina fiscellaria (Gn.) (Lepidoptera: Geometridae)

Abstract: The hemlock looper, Lambdina fiscellaria (Gn.), is a recurring major forest pest that is widely distributed in North America. Three subspecies (L. f. fiscellaria, L. f. lugubrosa (Hulst) and L. f. somniaria (Hulst)) have been recognized based on larval host or adult pheromone differences, but no consistent morphological differences have been reported. To clarify their taxonomic status, we surveyed mitochondrial DNA (mtDNA) sequence and restriction site variation in two protein coding genes, cytochrome oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Because milkweed herbivores, including these beetles, are thus likely to be of young to moderate geological age, I chose to sequence a mitochondrial gene of ostensibly suitable rate in these insects, the locus encoding subunit I of the terminal electron transport enzyme cytochrome oxidase (COI). COI has proved useful in resolving relationships among closely related species and genera of insects and other arthropods (Juan et al, 1995;Sperling et al, 1995Sperling et al, , 1996Sperling et al, , 1999Lunt et al, 1996;Willett et al, 1997;Knowlton and Weigt, 1998;Sandoval et al, 1998;Wells and Sperling, 1999;Caterino and Sperling, 1999;Dobler and Farrell, 1999;Funk, 1999;Harrison and Crespi, 1999;Moran et al, 1999). As the largest and most conservative proteincoding mitochondrial gene in insects (Crozier and Crozier, 1993), COI is potentially well suited to establishing a temporal framework for comparative studies of at least Cenozoic insect faunas, including the insects that attack Tertiary-originating lineages such as milkweeds (Dobler and Farrell, 1999), yuccas (Pellmyr and Leebens-Mack, 1999), and Asteraceace .…”
Section: Introductionmentioning
confidence: 99%
“…Because milkweed herbivores, including these beetles, are thus likely to be of young to moderate geological age, I chose to sequence a mitochondrial gene of ostensibly suitable rate in these insects, the locus encoding subunit I of the terminal electron transport enzyme cytochrome oxidase (COI). COI has proved useful in resolving relationships among closely related species and genera of insects and other arthropods (Juan et al, 1995;Sperling et al, 1995Sperling et al, , 1996Sperling et al, , 1999Lunt et al, 1996;Willett et al, 1997;Knowlton and Weigt, 1998;Sandoval et al, 1998;Wells and Sperling, 1999;Caterino and Sperling, 1999;Dobler and Farrell, 1999;Funk, 1999;Harrison and Crespi, 1999;Moran et al, 1999). As the largest and most conservative proteincoding mitochondrial gene in insects (Crozier and Crozier, 1993), COI is potentially well suited to establishing a temporal framework for comparative studies of at least Cenozoic insect faunas, including the insects that attack Tertiary-originating lineages such as milkweeds (Dobler and Farrell, 1999), yuccas (Pellmyr and Leebens-Mack, 1999), and Asteraceace .…”
Section: Introductionmentioning
confidence: 99%
“…These results are in contrast to many other phylogeographic studies of Lepidoptera in North America, which have found some genetic structure on a continental scale. Sperling et al (1998) found that mtDNA sequence variation of the hemlock looper, Lambdina fiscellaria (Geometridae), revealed two major lineages that were associated with either eastern or western populations. Similarly, Sperling and Harrison (1994) found geographic structure for mtDNA variation in Papilio zelicaon.…”
Section: Historymentioning
confidence: 99%
“…lineages of insects within a species, which are confined to a single host plant. A number of genetic studies have already shown that some host races can be recognised by distinct mitochondrial haplotypes (Brown et al 1996;Dobler & Farrell 1999;Shufran et al 2000;Sperling et al 1999). This finding indicates that the specific insect-plant relationship must have evolved some time ago because the occurrence of nucleotide substitutions, which characterise the haplotypes, is time dependent.…”
Section: Introductionmentioning
confidence: 99%
“…But also the alternative has been documented: Boulding (1998) found no evidence for phylogenetically distinct host races in the pea aphid (Acyrthosiphon pisum) indicating a more recent or no consistent host plant selection. It is a matter of debate whether the genetically defined host races should be considered as an indication of genetic polymorphism within a single species without clear subspecific divisions, or as evidence for sibling or multiple cryptic species (Sperling et al 1999;Adams & Funk 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation